THE EFFECT OF INVESTMENT KNOWLEDGE ON STUDENT'S INTEREST IN INVESTING SHARIA SHARE (An-Nisbah: Jurnal Ekonomi Syariah, 2022)
Investment can be  interpreted  as  an  activity to invest    in  both  money  and objects in an object with the aim of obtaining profits over a certain period. Investment decisions   are    a  very  important  decision  in  investing, where in order to get a profit we have to deal with  risk, therefore investors must evaluate the relationship between return  and  risk. This type of research is associative. The data used is primary data obtained through the dissemination of questionnaires to 264  student respondents of the Sharia Economic Law  study program of the Faculty of Sharia and  legal sciences  UIN SATU  Tulungagung. The sampling method used by researchers in each study program is proportionate stratified random sampling. The results  show  that the coefficient value of the variable parameters of investment  knowledge is 1.61  which  means that any  increase in the value  of  knowledge  or  understanding  of  investment    will  increase one's interest.   in  investing.   This  means that there is a  positive  linear  relationship  between  one's  knowledge  and  one's  interest  in  making  investments. The higher the knowledge a person knows investing,  the    higher  one's  interest  in  investing. The result of measuring the goodness of the model is to use the value of the coefficient of determination R2  which shows a number of 48.6%. The value  can be  interpreted  that the model  is able to  explain  the actual condition of only 48.6% where the remaining 51.4%  of a person's interest in investing is influenced by other variables outside the investment knowledge  variable..
Keywords: Knowledge, Student Interests, Stock Investment